1756. Prediction of Bloodstream Infection Prior to Onset of Symptoms by Plasma Metagenomic Sequencing in Pediatric Patients With Relapsed or Refractory Malignancy (PREDSEQ). (26th November 2018) - Goggin, Kathryn; Inaba, Yuki; Gonzalez-Pena, Veronica; Allison, Kim J; Chan, Ka Lok; Hollemon, Desiree; Ahmed, Asim; Hong, David; Maron, Gabriela; Hayden, Randall; Choi, John; Rubnitz, Jeffrey; et al.
Abstract: Background: Patients undergoing treatment for relapsed or refractory malignancies are at high risk of life-threatening bloodstream infection (BSI). A predictive screening test for BSI might allow pre-emptive therapy, but no validated test is currently available. We tested the hypothesis that plasma metagenomic next generation pathogen sequencing (NGS) would predict BSI before the onset of attributable symptoms. Methods: We enrolled 31 pediatric patients receiving for treatment relapsed or refractory malignancy in an IRB-approved prospective cohort study (PREDSEQ) of predictive sequencing. Episodes of febrile neutropenia or documented infection were collected prospectively from the medical record. BSI was defined according to NHSN criteria. Control Samples were defined as samples collected ≥7 clear days before or after any fever or documented infection. Residual clinical samples were stored for NGS; after filtering human sequences, reads were aligned to a curated pathogen database, and organisms above a predefined threshold were reported (Karius Inc., Redwood City, CA). Only bacteria and fungi were included in this analysis. Results: A total of 11 BSI episodes occurred in 9 participants (Table 1) during the study period. Predictive sensitivity of NGS in the 2 days before onset of infection ( n = 9) was 78% (95% CI 45–94%), and diagnostic sensitivity on the day of infection ( n = 11) was 82% (95% CI 52–95%). Specificity of NGS for development of fever or infection within 7 days ( n = 16) was 81% (95% CI 57–93%). NGS was positive up to 6 days prior to onset of BSI. In samples collected before or during documented infections, NGS also identified additional bacteria and fungi that were not detected by standard clinical testing. Conclusion: Plasma NGS shows promise for the detection of BSI prior to onset of symptoms in high-risk patients. Disclosures: K. Goggin, Karius Inc.: Investigator, Research support. K. L. Chan, Karius Inc.: Employee, Salary. D. Hollemon, Karius Inc.: Employee, Salary. A. Ahmed, Karius, Inc.: Employee, Salary. D. Hong, Karius, Inc.: Employee, Salary. R. Hayden, Roche Molecular: Scientific Advisor, Consulting fee. Abbott Molecular: Scientific Advisor, Consulting fee. Quidel: Scientific Advisor, Consulting fee. C. Gawad, Karius Inc.: Investigator, Research support. J. Wolf, Karius Inc.: Investigator, Research support.